2011
DOI: 10.1007/s00209-011-0841-7
|View full text |Cite
|
Sign up to set email alerts
|

On the Adams–Riemann–Roch theorem in positive characteristic

Abstract: We give a new proof of the Adams-Riemann-Roch theorem for a smooth projective morphism X → Y , in the situation where Y is a regular scheme, which is quasi-projective over F p . We also partially answer a question of B. Köck.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…It can be showed that τ (E) satisfies the defining properties of the p-th Bott element. In other words, we have the following proposition (see [PR12], Prop. 2.6).…”
Section: The Adams Riemann Roch Theorem In Positive Characteristicmentioning
confidence: 92%
See 4 more Smart Citations
“…It can be showed that τ (E) satisfies the defining properties of the p-th Bott element. In other words, we have the following proposition (see [PR12], Prop. 2.6).…”
Section: The Adams Riemann Roch Theorem In Positive Characteristicmentioning
confidence: 92%
“…The all ingredient will be used in Section 4. On a quasi-compact scheme of characteristic p > 0, Pink and Rössler constructed an explicit representative of the p-th Bott element (see [PR12], Sect. 2).…”
Section: The Adams Riemann Roch Theorem In Positive Characteristicmentioning
confidence: 99%
See 3 more Smart Citations